Development of Automated "Hexagonal Obstacle Test" in Sports Agility Measurement - Dzihan Khilmi Ayu Firdausi; Muhammad Eka Mardyansyah Simbolon (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
The measurement of agility in sports using the "hexagonal obstacle test" which used a stopwatch with human assistance as a tester is believed to be less objective.  In general, this research aims to develop an agility measurement instrument "Hexagonal Obstacle Test" which is able to measure a person's agility electronically and more objectively. Specifically, this research aims to: (1) replace conventional agility measurement, because this measuring instrument will work electronically; (2) developing a hexagonal obstacle test that works electronically by utilizing Infrared (IR)/ Laser Diode and Real-Time Clock (RTC) technology so that it is processed by a microcontroller so that the test is carried out automatically; (3) developing a hexagonal obstacle test that is more modern, practical, effective, objective and efficient. This study uses a research and product development approach which consists of several steps, namely observation, planning and design, experimentation and testing, and analysis. The results of data analysis showed that the product validity value was 0.975146897 and the product reliability value was 0.995983936. We conclude that the hexagonal obstacle test automation product is valid and reliable for measuring agility.